Judicial analysis of the determination of sanctions for money politics in legislative elections during the campaign in the city of Serang - Anjelika, Julia; Asnawi, Asnawi; Maulana, Ayang Fristia (Institute Of computer Science (IOCS), 2024)
Indonesia is a democratic country that has the concept of supreme sovereignty in the hands of the people. elections are a form of political participation of the people in a democratic country, so the integrity and fairness in organizing elections reflect the quality of democracy. In the general election system, political problems that often occur, one of which is Money Politics. The purpose of this study is to determine the judicial analysis of the determination of sanctions for money politics in the legislative elections during the campaign in Serang City based on Law No. 7 of 2017 concerning Elections. In this research, the approach taken is a qualitative approach. The research method used by the author in this research is literature study. In this study, in addition to primary data, researchers also used secondary data in the form of literature, namely books, journals, internet sites, and legislation related to the research. Based on the results of the research, it was found that the action in the form of sanctions against money politics during the legislative election campaign period in Serang City was still ineffective in carrying out its duties, marked by the lack of socialization in several areas and the many reports, complaints and findings received by Bawaslu Serang City related to the problem of money politics in the legislative elections but none were successfully handled based on existing legal procedures.